2006
DOI: 10.1097/01.iae.0000250006.76155.3d
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Persistent Macular Holes Using “Heavy Silicone Oil” as Intraocular Tamponade

Abstract: HSO can be a useful tool in the treatment of persistent macular hole. OCT images showed that the tamponade was effective in the upright position in the foveal region. OCT allowed determination of the time of tamponade removal according to the anatomical stage of hole closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 15 publications
2
50
1
3
Order By: Relevance
“…It has been used in several clinical series for the treatment of complicated RRD and recurrent macular hole. 20,27,32,35,49,50 The substance was removed on average after 2 months and complication rates seem to be significantly lower compared to F6H8 or other earlier tamponades. However, significant rates of emulsification and a rise in IOP could still be noticed.…”
Section: Heavy Silicone Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in several clinical series for the treatment of complicated RRD and recurrent macular hole. 20,27,32,35,49,50 The substance was removed on average after 2 months and complication rates seem to be significantly lower compared to F6H8 or other earlier tamponades. However, significant rates of emulsification and a rise in IOP could still be noticed.…”
Section: Heavy Silicone Oilsmentioning
confidence: 99%
“…[20][21][22]27,32,33 Another subgroup is myopic patients with RRD associated with a macular hole, a posterior staphyloma, or recurrent macular holes. 11,12,21,26,34,35,50 Uncommon indications that were included into clinical trials as single cases only were tractional RD associated with diabetic retinopathy, 6,11,14,15 hypotony, 11 and retinal necrosis. 6 Few patients with breaks in the superior periphery in addition to inferior pathology have been treated with heavy tamponades.…”
Section: Indicationsmentioning
confidence: 99%
“…Rizzo et al achived success of reoperation using "heavy silicon oil" (ref. 10 ). This type of tamponade was effective even in the upright position.…”
Section: Discussionmentioning
confidence: 99%
“…In both patients, the macular hole closed and visual acuity improved from 20/200 to 20/40 and from 20/600 to 20/100. No complications were reported [89]. Lappas et al [90] treated 12 patients with macular hole persisting after the standard procedure.…”
Section: Endotamponades Heavier Than Watermentioning
confidence: 99%
“…Jonas and Jager [88] used F 6 H 8 for the retreatment of a patient with persistent macular hole, but had significant complication after 4 weeks (epiretinal membrane on the surface of the complete retina and emulsification); however, the macular hole was closed and visual acuity increased from 20/200 to 20/60. Rizzo et al [89] reported on 2 cases that were treated with vitrectomy, repeat ILM peeling and heavy endotamponade (Oxane HD) for recurrent macular hole after the standard procedure. In both patients, the macular hole closed and visual acuity improved from 20/200 to 20/40 and from 20/600 to 20/100.…”
Section: Endotamponades Heavier Than Watermentioning
confidence: 99%